Perancangan Dan Pembuatan Mesin Penghancur Botol Plastik Elektronik - Prakoso, Bima Agung; , Ir. Pratomo Budi Santoso, MT; , Umi Fadilah, ST, MEng (2016)
Today many of the problems caused by waste plastic waste , because of the nature of the elements which are difficult to be processed by decomposing microorganisms present in the soil . However, there are several types of plastic that can be collected to be sold back to the manufacturer via the scavenger and distributors . One is a plastic bottle. Until now , scavengers still collecting plastic water bottle in one piece in a sack which is then sold to distributors to be brought to the mill and processed . In the processing of plastic bottles by means chopping up into small pieces , which are usually carried out by using a pair of scissors or a knife . Based on observations in the field that had only 3 kg in three sacks , with enumerated will be gained about 3 kg in a single sack . This means saving up to 2 -fold a sack . This study of the plastic bottle crusher , crushed with a knife and equipped with LCD data display and controlled using the Arduino powered by 3 -phase AC motors . The way the device works by turning switch , then push the button one who serves as star / stop , two buttons as research . Results from waste plastic bottles will be displayed on the LCD in the form of a gram. The results of this study can be concluded with a ratio of weight of the bottle before it is destroyed or had been destroyed ie by weighing the measuring devices of conventional and measuring devices tool made , the first result is average and percent of results before weighed and after weighed measuring devices of conventional 3 , 6 grams and 2.58 % , yields for both average and percent results were weighed before and after the weighed measuring devices tool created 3,794 grams and 2.76% , for the third result is average and percent before the results were weighed by the measuring instrument conventional and weighed with a measuring tool made 0.516 grams and 0.304 % , the result fourth average and percent after the results were weighed by measuring and weighed with a measuring instrument made 0.71 grams and 0,384 % . So the results of measurements with conventional measuring instruments with a measuring instrument that made the difference was not much different so this measure either . Keywords : Arduino , Speed High , Electronic Waste Crusher Machine ,.